The Development of Educational YouTube Videos-Based Learning Media: Learners’ Need Analysis - Ilyas, Muhammad; Syarif, Hermawati; Refnaldi; Miranti Eka Putri; Oliver, Jonathan (International Journal of Language Pedagogy, 2023)
This study aims to analyze the needs of students in learning in the speaking for general communication course in order to develop Educational YouTube Videos-based learning media. The integration of YouTube in learning speaking can be a valid resource for teaching lecturers to improve their lessons with various types of content that are interesting and useful and in accordance with the material being taught, and this integration is also expected to motivate students to learn. This study uses a qualitative research design by distributing questionnaires and interviews to find out the problems that occur in the learning process and what students want in improving their speaking skills. As a result, students still experience problems in speaking ability, but the biggest problem students’ face is related to fluency. With regard to the problem of fluency, the results of the interviews show that the desired way of learning is that students want to be more able to practice speaking by having lots of dialogue and direct interaction, displaying unique videos related to the material being taught so that it is not boring and can be understood easily. Easy, using YouTube videos to get used to listening to native speakers speak more. Learning will be more interesting if film media is added, such as identifying clips from a film.